Sightsinging complete - Benward, Bruce; Carr, Maureen A. (Boston McGraw-Hill Humanities/Social Sciences/Languages, 1999)
Designed for the sight singing component of the Freshman and Sophomore music major curriculum, Sight Singing Complete presents the essential components of this sometimes difficult skill in a practical and effective manner. "Hearing music with one's eyes" has served as the theme of Sight Singing Complete since the first edition. In order to reach this goal, the sequence of instructional material is designed to help students develop the aural skills that will enable them to reverse the compositional process of sound into symbol to one of symbol into sound. The comprehensive and systematic approach employs literature, drawing most of the examples from actual pieces instead of devising contrived melodies. The abundant new exercises in this edition refresh the text, even as the proven exercises continue to educate students.Show More Show Less